Phuan Fusion Recipe: Upgrading Thai Phuan’s Cuisine for Tourism in Hat Siao Sub-district, Sukhothai Province, Thailand - Panyayong, Chunkamol; Raksarikorn, Chawalit; Panyayong, Taweesit (Area Based Development Research Journal, 2024)
In Hat Siao Sub-district, Si Satchanalai District, Sukhothai Province of Thailand, there exists a unique style of Thai Phuan food characterized by its use of local ingredients such as fish, vegetables, and seasonal forest products. This culinary tradition emphasizes simplicity and natural flavors, avoiding the use of artificial additives. Despite the rich culinary heritage, efforts to attract tourists to this area have been lacking. This study aims to address this gap by developing Phuan Fusion food recipes tailored for tourism and creating innovative tourism activities centered around Phuan Fusion cooking. The key objectives include: 1) developing Phuan Fusion recipes that appeal to different types of tourists, 2) creating engaging tourism activities to showcase Phuan Fusion cooking, 3) enhancing the capabilities and potential of network partners involved in tourism, 4) testing the effectiveness of the developed tourism activities, 5) collaborating and learning with network partners to improve the tourism offerings. The study has identified 15 Phuan Fusion food recipes that cater to six types of tourists, along with three travel routes. Additionally, Good Agricultural Practices have been implemented, and farm stay options have been introduced to enhance the tourism experience. The innovative tourism activities include guided tours to orange orchards with demonstrations of safe agricultural practices, Phuan Fusion food cooking classes, and an immersive experience showcasing Phuan Fusion food preparation. As a result of these efforts, the community has been able to preserve the identity of traditional Thai Phuan food while creating new Phuan Fusion recipes tailored for creative tourism activities. This has had a positive economic impact, with each tourist contributing an income of 580 Baht (approximately 15.70 USD), leading to a monthly increase in community income of 48,333 Baht (approximately 1308 USD).